2022
DOI: 10.1002/hed.27053
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PDK1 enhances radiosensitivity and reverses epithelial–mesenchymal transition in nasopharyngeal carcinoma

Abstract: Background Radioresistance challenges the clinical outcomes of nasopharyngeal carcinoma (NPC). The 3‐phosphoinositide‐dependent protein kinase 1 (PDK1) is a crucial kinase of PI3K/AKT signaling pathway which has been implicated in the process of radioresistance. However, the role of PDK1 in NPC remains largely unclear. Methods The expression of PDK1 was determined by immunohistochemistry and Western blot. The effects of RNA interference and pharmacologic inhibitor of PDK1 in combination with irradiation were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Similarly, PDK1 overexpression is correlated with poor prognosis in nasopharyngeal carcinoma patients, and PDK1 depletion augments radiosensitivity of nasopharyngeal carcinoma cells. 27 In summary, this study supported that HOXA11-AS maintained stem cell stemness by targeting the miR-518a-3p/PDK1 axis, thus reducing cell radiosensitivity in OSCC, which provided a theoretical basis for basic research of radiotherapy tolerance mechanisms of OSCC. However, this study only discussed the mechanism in animal experiments.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similarly, PDK1 overexpression is correlated with poor prognosis in nasopharyngeal carcinoma patients, and PDK1 depletion augments radiosensitivity of nasopharyngeal carcinoma cells. 27 In summary, this study supported that HOXA11-AS maintained stem cell stemness by targeting the miR-518a-3p/PDK1 axis, thus reducing cell radiosensitivity in OSCC, which provided a theoretical basis for basic research of radiotherapy tolerance mechanisms of OSCC. However, this study only discussed the mechanism in animal experiments.…”
Section: Discussionsupporting
confidence: 67%
“…We silenced HOXA11‐AS and overexpressed PDK1 in SCC15 cells and found overexpression of PDK1 partially abrogated the effects of HOXA11‐AS knockdown on stemness and cell radiosensitivity of OSCC cells. Similarly, PDK1 overexpression is correlated with poor prognosis in nasopharyngeal carcinoma patients, and PDK1 depletion augments radiosensitivity of nasopharyngeal carcinoma cells 27 …”
Section: Discussionmentioning
confidence: 99%
“…Combined with our study, these results showed that Dcr3 may be an important molecule in the regulation of radioresistance of lung cancer cells. Numerous studies have suggested the involvement of AKT/GSK-3β pathway in radioresistance [35][36][37][38]. Using the AKT inhibitor MK-2206, we revealed that the inhibition of AKT/GSK-3β pathway was responsible for the effect of OMT on radiosensitivity.…”
Section: P R E P R I N Tmentioning
confidence: 79%
“…The PI3K/Akt signaling pathway activates Nrf2 and inhibits ROS levels ( Zhang et al, 2016 ; Liu et al, 2020 ). PDPK1 phosphorylates Akt Thr308, while Akt Ser473 is activated by integrin-linked proteins, thereby activating a variety of downstream target proteins ( Mamidi et al, 2022 ; Zhang et al, 2022b ). Our results showed that Deh suppressed PDPK1 protein expression and induced the Akt/Nrf2 signaling pathway to reduce ROS production in mitochondria.…”
Section: Discussionmentioning
confidence: 99%